VIEWS OF JUNIOR HIGH SCHOOL TEACHERS TOWARD ONLINE LEARNING - Juhji, Juhji; Sutarman, Adang; Raharjo, Supadiyo (Idaarah: Jurnal Manajemen Pendidikan, 2021)
Abstract: Views of Junior High School Toward Online Learning This study aims to explore the views of junior high school teachers on online learning. The survey method is used to gather the views of junior high school teachers in Serang Regency. Seventy-nine teachers who had taught at the junior high school level, consisting of 37 male teachers and 42 female teachers were asked questions via Google Form. The results showed the use of Whatsapp Group is more dominant than other online media because its use is more familiar and accessible to students. In general, teacher’s views on online learning are moderate, although there are some items that indicate a high category. Further discussions regarding online learning are presented at the end and some of the advantages of online learning are discussed in depth. Abstrak: Pandangan para Guru Sekolah Menengah Pertama terhadap Pembelajaran Daring Penelitian ini bertujuan mengeksplorasi pandangan para guru sekolah menengah pertama terhadap pembelajaran daring. Metode survei digunakan untuk mengumpulkan pandangan para guru sekolah menengah pertama di Kabupaten Serang. Tujuh puluh sembilan guru yang telah mengajar di tingkat sekolah menengah pertama, terdiri atas 37 guru laki-laki dan 42 guru perempuan diberikan pertanyaan melalui Google Form. Hasil penelitian menunjukkan penggunaan Whatsapp Group lebih dominan daripada media daring yang lainnya karena penggunaannya lebih familiar dan mudah dijangkau peserta didik. Secara umum, pandangan guru terhadap pembelajaran daring berkategori sedang, meski ada beberapa item yang menunjukkan kategori tinggi. Diskusi lanjut terkait pembelajaran daring disajikan pada bagian akhir dan beberapa keunggulan pembelajaran daring dibahas secara mendalam.